2014
DOI: 10.1111/jch.12381
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Gamma‐Glutamyltransferase Levels and Prehypertension in Chinese Adults: The Cardiometabolic Risk in Chinese Study

Abstract: The authors aimed to investigate the relationship between serum gamma-glutamyltransferase (GGT) and prehyperten-sion, as well as the modification of other metabolic risk factors in a large cohort of Chinese individuals. The data were collected via a community-based health examination survey in central China. Blood pressure, body mass index (BMI), and levels of GGT, fasting blood glucose, aspartate aminotrans-ferase (AST), alanine aminotransferase (ALT), and lipid indicators were measured. In total, data from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…Which suggested that glutamine could improve the protein metabolism of X. davidi. Similar effects were also observed in juvenile hybrid sturgeon (Acipenser schrenckii × Huso dauricus ) (Zhu, et al, 2010) and mirror carp (Song, et al, 2016). Appropriate levels of glutamine supplementation were associated with a signi cant decrease in plasma TC and TG concentrations in X. davidi, suggesting an improvement in lipid metabolism.…”
Section: Discussionsupporting
confidence: 57%
“…Which suggested that glutamine could improve the protein metabolism of X. davidi. Similar effects were also observed in juvenile hybrid sturgeon (Acipenser schrenckii × Huso dauricus ) (Zhu, et al, 2010) and mirror carp (Song, et al, 2016). Appropriate levels of glutamine supplementation were associated with a signi cant decrease in plasma TC and TG concentrations in X. davidi, suggesting an improvement in lipid metabolism.…”
Section: Discussionsupporting
confidence: 57%
“…We also observed an increasing trend for the mean levels of ALT, AST and GGT in the prehypertension and hypertensive group compared to the normotensive group. Higher levels of GGT were previously reported in prehypertensive Korean, Japanese, Chinese, and US adults [33][34][35][36].…”
Section: Discussionmentioning
confidence: 50%